Identifikasi Waste pada Produksi Kayu Lapis dengan Pendekatan Lean Manufacturing untuk Meningkatkan Kualitas Proses Produksi (Studi Kasus : PT Sumber Mas Indah Plywood) - Miftahus Shomad; Rakhmawati Rakhmawati; Supriyanto Supriyanto (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
This research aimed at identifying the wastes of plywood production in PT Sumber MasIndah Plywood. Results were then utilized to determine methods in reducing wastes. Theidentification of waste was carried out using lean manufacturing approach. The data werecollected from manufacturer records, study to determine processing time, as well as interviewand quisioners which were distributed to workers in each department. Big picture mapping andvalue stream mapping tools (VALSAT) were then utilized to process the data. Results ofanalyses using big picture mapping showed that total production lead time was 438,8 minutes,with 235,97 minutes of them were value added activities; and 27 days of total information leadtime. Workshop waste analyses resulted in the highest waste generated during plywoodproduction process. Those were 133 waiting time (delay), 113 defect and 78 excessivetransportation. Further analyses using VALSAT showed three methods to identify the data inmore detail, namely process activity mapping (PAM), supply chain response matrix (SCRM)and quality filter mapping (QFM). Results from PAM method revealed 125 activities duringproduction, consist 62 value added activities, 33 necessary but non value added activities and 30non value added activities. While results from SCRM showed the average 22,63 days of totalorder fulfillment process comprised of 4,13 days of total physical stock and 18,5 days of totallead time. QFM result showed ratio of scrap defect reject 0,4% and ratio of scrap defect UTY3,46%. In general waste in plywood production at PT Sumber Mas Indah Plywood wasgenerated from worker, material, machinery, methods and environment. One of the ways toimprove it is by applying pull system (Kanban)